Smart nanoparticle delivery of cancer vaccines enhances tumor immune responses: a review - Qiu, Jiayou; Wu, Chenghu (Frontiers in Nanotechnology, 2025)
Cancer arises from the uncontrolled proliferation of tumor cells within the body. As the incidence of cancer continues to rise, its treatment has become a critical focus for clinicians. The body possesses a tumor immune surveillance mechanism designed to inhibit the proliferation of tumor cells. When tumor-associated mutant antigens appear on the cell surface, antigen-presenting cells, as dendritic cells, present these specific antigens to immune cells, such as T lymphocytes, thereby promoting an immune response and enhancing the cytotoxic effect on tumor cells. Concurrently, the immune system develops immune memory, akin to the response elicited by vaccination. While traditional diseases like tuberculosis and tetanus can be prevented and treated through vaccination, the development of cancer vaccines remains in its nascent stages. Tumor-specific antigens for cancer vaccines can originate from the patient’s own tumor cells or be generated through mutation. Thus, enhancing the presentation of tumor-specific antigens to immune cells is pivotal in anti-tumor immunotherapy. Advances in nanoscience offer novel approaches to tumor immunotherapy. Nanoparticles (NPs) engineered through nanotechnology have garnered significant attention due to their diverse, favorable, and stable properties. These NPs can effectively encapsulate chemotherapy drugs and proteins, facilitating targeted delivery in vivo. Common NPs carriers include liposomes, polymeric nanoparticles, and metal nanoparticles, among others. The development of intelligent NPs delivery systems can enhance efficient antigen presentation, thereby augmenting tumor immune responses. Tumor-specific antigens can be sourced from tumor cells or generated through mutation. In this review, we summarize current methodologies for obtaining various tumor-specific antigens and discuss how these antigens can be delivered to immune cells via different intelligent NPs to bolster anti-tumor immunity. Additionally, from a clinical translation perspective, we explore the challenges and opportunities associated with enhancing tumor immune responses through the smart NP delivery of cancer vaccines. We aim for this review to inspire new strategies in cancer treatment through the use of intelligent NPs and to advance research in cancer vaccines.